Asian Ecumenical Contributions to Theologies of Justice and Peace - Rajkumar, Peniel (The ecumenical review, 2017)
Issues of justice and peace have been at the centre of Asian ecumenical theology, which has developed within the context of the Asian reality of multi-religiosity, on the one hand, and rampant poverty, on the other. This article examines how Asian ecumenical theological expressions, such as Dalit theology from India, Minjung theology from Korea, the many Asian womanist theologies, indigenous theologies, the theology of struggle from the Philippines, Burakumin theologies from Japan, and homeland theology from Taiwan, have sought to engage with these realities. It examines the impact of socio-political movements on theological formation through a focus on the life and work of the Indian ecumenical leader M. M. Thomas, and offers a detailed examination of Dalit and Minjung theologies as expressions of the Asian ecumenical theological engagement with justice.